Hepatoprotective effects of Common Sage (Salvia officinalis) leaves on Cyanide-Induced Hepatotoxicity in Male Wistar Rats - Azukaego Thomas Hughs Mokogwu; Emeka Edward Okocha; Kingsley Chukwuka Amaihunwa; Enekabokom Nwoke Ekene; Benson O Eyenubo; Osinachi Mark Nwachukwu; Ikemefune Ochonogor; Godwin O Avwioro (International Journal of Human and Health Sciences (IJHHS), 2026)
Common sage (Salvia officinalis) leaf is used worldwide as a medicinal plant for various ailments. Its hepatoprotective effect was investigated on cyanide-induced hepatotoxicity in rats. In this experimental study, thirty male Wistar rats, divided into five groups having six rats in each group (A, B, C, D and E). Group A which was the control, received 0.4ml/day corn oil, while group B had 0.4ml of potassium cyanide (7mg/kg/day) and group C received 0.4ml of sage plant leaf extract (500mg/kg/day) in saline. Group D received 0.4 ml sage plant leaf extract (500mg/kg/day) plus 0.4 ml potassium cyanide (7mg/kg/day) and group E received 0.4ml of sodium thiosulphate (Na2S2O3) (600 mg/kg/day) plus 0.4ml of potassium cyanide (7mg/kg/day). Treatments were by oral route, daily, and weighed at intervals of 2 days for two weeks. Serum aspartate transaminase (AST), alanine transaminase (ALT), gamma-glutamyl transferase (GGT), alkaline phosphatase) (ALP) activity and total proteins (TP) and total bilirubin (TB) were measured as liver function indicators. While liver malondialdehyde (MDA) and Superoxide Dismutase (SOD), glutathione- S-transferase (GST), reduced glutathione (GSH) and catalase were assessed as indices of oxidative stress. Standard methods were utilized for all the measurement. The increased activities of the liver function enzymes by cyanide-induction were restored by co-administration of either the sage (Salvia officinalis) leaf or sodium thiosulphate (Na2S2O3). The MDA level which was increased with reduced activities of GSH, GST, SOD and catalase on treatment with cyanide only, were all reversed on co-treatment of cyanide with sage leaf extract or chemical drug (sodium thiosulphate). The results revealed that common sage leaf protects the liver against cyanide-induced oxidative stress. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 227-235